First record of Rhipsalis oblonga (Cactaceae), a threatened plant species, in Minas Gerais state, Brazil - Diego Gonzaga; Daniel Barbosa; Geicilaine Basílio; Fernando da Silva; Luiz Menini Neto (Check List, 2015)
We present the first record of Rhipsalis oblonga in Minas Gerais state, Brazil. This record suggests that this species, having a global rank of Vulnerable, is nevertheless threatened in Minas Gerais with extirpation due to the small area of occupancy that is outside of any conservation unit. We present morphological data for this species and comment on its ecology and distribution.